Perilaku Harian Buaya Muara (Crocodylus porosus) sebagai Indikator dan Parameter Penentu Pelepasliaran di Alam Bebas - Karubun, Jemy Piter (LPPM Universitas Terbuka, 2025)
Estuaria crocodiles (Crocodylus porosus) are wild animals protected under Law No.32 of 2024 to ensure the maintenance of their population, even though their conservation status is categorized as Least Concern (LC), indicating a low risk of extinction. This study aims to observe the daily behavior of estuarine crocodiles (Crocodylus porosus) at the Tegal Alur Animal Rescue Center, under the Natural Resources Conservation Agency of Jakarta. The data obtained are expected to serve as a reference for assessing the readiness and suitability of estuarine crocodiles to be released into their natural habitat. The study employed the focal animal sampling method, observaing daily behavioral parameters such as movement, feeding habits, social interactions, and basking behavior. The research sample consisted of two estuarine crocodiles: one adult female and one adult male. The data were analyzed to determine the percentage of daily behaviors and their relationship to environmental factors, particularly cage conditions. The results showed that daily behaviour of estuarine crocodiles at the Tegal Alur Animal Rescue Center generally reflects the typical lifestyle patterns of crocodiles in the wild. However, their movement is less unrestricted compared to crocodiles in their natural habits. Observed activities including moving, walking, or crawling between dry and wet areas; feeding behaviors such as catching, biting, positioning, and swallowing food; social behaviors like vocalizations and aggressive interactions when disturbed by other crocodiles; and basking behaviors, such as opening their mouths and quickly moving their front and hind legs and tail. In conclusion, the overall life activities of the estuarine crocodiles at the Tegal Alur Animal Rescue Center suggest that they retain natural behaviors, making them suitable for release back into their natural habitats.